Readiness for Childbirth in Primigravida Trimester III Pregnant Women at the Spirit of Internal Health Center, Barito Kuala District - Mariyana Mariyana (Jurnal EduHealth, 2023)
The high maternal mortality rate (MMR) in Indonesia still occurs today. Ministry of Health data shows that there were 6,856 maternal deaths in 2021, an increase from the previous 4,197 maternal deaths in 2019, while the Kab. Barito Kuala in 2020 The maternal mortality rate of 5 cases has increased compared to 2019, namely 0 cases. The aim of this study was to describe the factors of readiness for childbirth in third trimester primigravida pregnant women at the Spirit Health Center in Barito Kuala district. This research method is descriptive using a quantitative research design. The sampling technique used is Total Sampling. The sample that was the subject of the study was 20 primigravida pregnant women in their third trimester. The study period was from November to December 2022.